Eksplorasi Ketimpangan dan Klasterisasi Pembangunan Manusia di Provinsi Nusa Tenggara Timur - Dwi Rizky Syaifullah; Diah Mekita Sari (Badan Pusat Statistik Provinsi NTT, 2025)
The Human Development Index (HDI) is a crucial metric for assessing multidimensional regional development quality. Nusa Tenggara Timur Province (NTT) has one of the lowest HDI scores in Indonesia, reflecting persistent challenges in education, health, and economic conditions. This study examines HDI disparities in NTT and classifies its regencies/municipality using Coefficient Variation (CV) and K-means clustering. CV quantifies inequality among regencies/municipality, while K-means clustering segments regions based on HDI patterns. The novelty of this study lies in integrating CV analysis with K-means clustering, providing a more comprehensive approach to understanding HDI disparities. This combined method allows for a more detailed classification of regions, offering insights for more targeted policy interventions. The findings reveal a decline in HDI disparity from 2020 to 2024, primarily driven by improvements in the living standard dimension. However, significant gaps persist, particularly in education and health accessibility. The clustering analysis identifies four distinct regional groups: (1)